How does the energy consumption structure affect the green economic development? A spatial impact analysis - Zhang, Shumin; Wang, Jing; Guan, Jiawei (Frontiers in Environmental Science, 2024)
Optimizing the structure of energy consumption (ECS) is conducive to promoting the improvement of efficiency and quality of regional green economic development (GED). This study utilizes panel data from 30 provinces in China from 2010 to 2021 to construct a comprehensive evaluation index of green economic development (GED) and adopts a spatial Durbin model to assess the impact of energy consumption structure (ECS) on GED. Results mainly showed that: (1) ECS improved GED and passed the significance test. (2) The ECS optimization had apparent spatial spillover effects. The optimization of ECS in this region promoted the GED of neighboring regions, which was more significant in central and western regions. (3) As for regional heterogeneity, the optimization effect of ECS on the region presents central region > western region > eastern region. (4) ECS affects GED through industrial structure optimization. It is crucial for structuring energy usage, improving human well-being, and fostering sustainable growth.